Targeted next‐generation sequencing approach for molecular genetic diagnosis of hereditary colorectal cancer: Identification of a novel single nucleotide germline insertion in adenomatous polyposis coli gene causes familial adenomatous polyposis. Issue 1 (6th December 2018) - Wang, Dan; Liang, Shengyun; Zhang, Xipeng; Dey, Subrata Kumar; Li, Yuwei; Xu, Chen; Yu, Yongjun; Li, Mingsen; Zhao, Guoru; Zhang, Zhao
Abstract: Background: Familial adenomatous polyposis (FAP) is an autosomal dominantly inherited disease which primarily manifested with developing adenomas or polyps in colon or rectum. It is caused by the germline mutations in adenomatous polyposis coli ( APC ) gene. Patients with FAP are usually manifested with "hundreds or even thousands" adenomas or polyps in colon or rectum. However, without proper clinical diagnosis and timely surgical interventions, colorectal adenomas, or polyps gradually increase in size and in numbers which finally leads to colorectal cancer (CRC) at the mean age of 36 years of the patient. Methods: In this study, we identified a family with FAP. In this family, FAP has been diagnosed clinically based on symptoms, medical test reports, and positive family history for three generations. In order to unveil the molecular genetic consequences underlying the disease phenotype, we performed next‐generation sequencing with a customized and designed panel of genes reported to be associated with hereditary CRC. The variant identified by next‐generation sequencing has been validated by Sanger sequencing. Results: A heterozygous novel insertion [c.3992_3993insA; p.Thr1332Asnfs*10] in exon 16 of APC gene has been identified. This novel insertion is cosegregated well with the FAP phenotype among all the affected members of this family. This mutation causes a frameshift by the formation of a premature stop codon which finally results in the formation of a truncated APC protein of 1, 342 amino acids instead of the wild type APC protein of 2, 843 amino acids. Hence, this is a loss‐of‐function mutation. This mutation was not found in unaffected family members or in normal control individuals. Conclusion: Our present study emphasizes the importance of a novel approach of the gene panel‐based high‐throughput sequencing technology for easy and rapid screening for patients with FAP or CRC which will help the clinician for follow‐up and management. Abstract : Our present study emphasizes the importance of a novel approach of the gene panel based high through‐put sequencing technology for easy and rapid screening for patients with familial adenomatous polyposis or colorectal cancer which will help the clinician for follow‐up and management.